2002
DOI: 10.1385/ijgc:32:2-3:165
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Colonic Ischemia Mimicking Carcinoma

Abstract: In this article, we describe a case of colonic ischemia masquerading as colonic carcinoma in a 75-yr-old female. Although this clinical diagnostic problem has been described before, it is rather unusual that the clinical, roentgenographical, endoscopic, and even histopathologic evaluation could not exclude carcinoma with certainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Significantly, the endoscopic features of ischaemic colitis can mimic those of colorectal carcinoma, with more extensive inflammatory masses/ulcerations appearing as neoplastic. There are multiple case reports in the literature of similar endoscopic presentations and subsequent endoscopic and histological outcomes [9,11,12]. This case is of particular interest because of a descending colonic mass lesion, which turned out not to be malignant.…”
Section: Discussionmentioning
confidence: 84%
“…Significantly, the endoscopic features of ischaemic colitis can mimic those of colorectal carcinoma, with more extensive inflammatory masses/ulcerations appearing as neoplastic. There are multiple case reports in the literature of similar endoscopic presentations and subsequent endoscopic and histological outcomes [9,11,12]. This case is of particular interest because of a descending colonic mass lesion, which turned out not to be malignant.…”
Section: Discussionmentioning
confidence: 84%
“…While the non-occlusive causes include septic shock, hemorrhage shock, heart failure, cardiac arrhythmias, hemodialysis and medications [ 4 ]. Approximately 20% of patients with ischemic colitis have a potentially obstructing lesion, such as colon cancer, diverticulitis or leiomyoma [ 5 ]. Furthermore, risk factors associated with the development of disorder are age, diabetes mellitus, dyslipidemia, heart failure, peripheral arterial disease and treatment with hypotensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2 previously reported cases showed resolution of the mass lesions 19 days after initial presentation. [7][8][9] Brandt et al 7 have previously suggested, predominantly on the basis of imaging findings, that the mass-like appearance may be due to submucosal edema and hemorrhage in cases that present with a polypoid mass and that submucosal or mural fibrosis with inflammatory granulation tissue may result in a malignant-appearing stricture in some cases. It has also been suggested that the polypoid mass-like presentation may represent an acute onset disease, whereas the stricture-like lesions may be a result of chronic low-grade ischemia and subsequent fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Occasionally, the diagnosis may not be straightforward because of atypical clinical or pathologic manifestations, and, in rare instances, ischemic colitis has been reported in association with a mass lesion mimicking malignancy. [7][8][9] This represents a challenging scenario because of the well-recognized association between colonic ischemia and colorectal carcinoma. 7,[10][11][12] Approximately 20% of colonic ischemia is associated with a benign or malignant obstructing mass, but in such cases the area of ischemia is typically either proximal to or within the region occupied by the mass lesion (so-called "obstructing colitis").…”
mentioning
confidence: 99%
See 1 more Smart Citation